Essentials of Statistics for the Behavioral Sciences, 10th Edition - Frederick J Gravetter; Larry B. Wallnau; Lori-Ann B. Forzano; James E. Witnauer (Cengage Learning, 2020)
Updated with the latest research, Gravetter/Wallnau/Forzano/Witnauer's ESSENTIALS OF STATISTICS FOR THE BEHAVIORAL SCIENCES, 10th Edition delivers straightforward instruction, hands-on learning tools and real-world examples to help you go beyond memorizing formulas to truly understanding the hows and whys of statistics. Giving extra focus to the topics students typically struggle with most, the authors take time to fully explain statistical concepts. Integrated applications reinforce concepts, offering further support to ensure that even those with a weak background in mathematics can fully grasp statistics. The authors also illustrate how an understanding of statistical procedures will help you comprehend published findings -- ultimately leading you to become a savvy consumer of information. Also available, the MindTap digital learning solution helps you learn on your own terms.